COMBINED EFFECT OF VITAMIN B (B6, B9, B12) AND POTASSIUM SUPPLEMENTATION ON STROKE IN RAT MODEL - Noman Aslam; Muhammad Imran Hussain; Khansa; Imran Nawaz Bhatti; Qaswara Affaf; Hafiza Iqra Akram; Sahir Shahzad; Tasbiha Irfan; Moha Akram Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Stroke is second most common cause of death and the third most common cause of disability worldwide. The burden of stroke is rising quickly in low and middle-income nations, many of which are ill-equipped to handle the problem it poses. The objective of the current study was to determine the combined effect of Vitamin B (B6, B9, B12) and Potassium supplementation on stroke in rat model. Methods:  Vitamin B (B6, B9, B12) and Potassium was bought in supplemented form. Rats were divided into five groups, including a control group Go). Complete Blood Count (CBC), Liver Function Test, Homocysteine Level and Blood Pressure were analyzed to check impact of B vitamins and potassium. The p-value